Sex differences in contributors to coronary microvascular dysfunction - Kwan, Alan C.; Wei, Janet; Ouyang, David; Ebinger, Joseph E.; Merz, C. Noel Bairey; Berman, Daniel; Cheng, Susan (Frontiers in Cardiovascular Medicine, 2023)
Background Coronary microvascular dysfunction (CMD) has differences in prevalence and presentation between women and men; however, we have limited understanding about underlying contributors to sex differences in CMD. Myocardial perfusion reserve index (MPRI), as semi-quantitative measure of myocardial perfusion derived from cardiac magnetic resonance (CMR) imaging has been validated as a measure of CMD. We sought to understand the sex differences in the relations between the MPRI and traditional measures of cardiovascular disease by CMR. Methods A retrospective analysis of a single-center cohort of patients receiving clinical stress CMR from 2015 to 2022 was performed. Patients with calculated MPRI and no visible perfusion defects consistent with obstructive epicardial coronary disease were included. We compared associations between MPRI versus traditional cardiovascular risk factors and markers of cardiac structure/function in sex-stratified populations using univariable and multivariable regression models. Results A total of 229 patients [193 female, 36 male, median age 57 (47–67) years] were included in the analysis. In the female population, no traditional cardiovascular risk factors were associated with MPRI, whereas in the male population, diabetes (β: −0.80, p = 0.03) and hyperlipidemia (β: −0.76, p = 0.006) were both associated with reduced MPRI in multivariable models. Multivariable models revealed significant associations between reduced MPRI and increased ascending aortic diameter (β: −0.42, p = 0.005) and T1 times (β: −0.0056, p = 0.03) in the male population, and increased T1 times (β: −0.0037, p = 0.006) and LVMI (β: −0.022, p = 0.0003) in the female population. Conclusion The findings suggest different underlying pathophysiology of CMD in men versus women, with lower MPRI in male patients fitting a more “traditional” atherosclerotic profile.